2021
DOI: 10.34172/ijhpm.2021.27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Pay-for-Performance Program on Renal Outcomes Among Patients With Early-Stage Chronic Kidney Disease in Taiwan

Abstract: Background: With the promising outcomes of the pre-ESRD (end-stage renal disease) pay-for-performance (P4P) program, the National Health Insurance Administration (NHIA) of Taiwan launched a P4P program for patients with early chronic kidney disease (CKD) in 2011, targeting CKD patients at stages 1, 2, and 3a. This study aimed to examine the long-term effect of the early-CKD P4P program on CKD progression. Methods: We conducted a matched cohort study using electronic medical records from a large healthcare deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
1
2
0
Order By: Relevance
“…The time for joining a P4P program was far longer than in the study mentioned above; therefore, this study found that the participation of diabetic patients in the program prolonged the time it would have taken to enter the stage of terminal renal disease, thus lowering the risk of dialysis significantly compared with non-participants. This result was consistent with the literature [61,62].…”
Section: Discussionsupporting
confidence: 94%
“…The time for joining a P4P program was far longer than in the study mentioned above; therefore, this study found that the participation of diabetic patients in the program prolonged the time it would have taken to enter the stage of terminal renal disease, thus lowering the risk of dialysis significantly compared with non-participants. This result was consistent with the literature [61,62].…”
Section: Discussionsupporting
confidence: 94%
“… 43 , 44 Empirical findings have also demonstrated that P4P programs in Taiwan have improved health outcomes in patients with diabetes, breast cancer, hepatitis B and C, and early chronic kidney disease; these improvements are associated with guideline adherence. 23 , 25 , 27 , 29 , 30 , 45 Taiwan’s COPD P4P program requires health care providers to provide patient-centered comprehensive care according to the Taiwan COPD guidelines, with additional financial bonuses for those who achieve high-quality performance on the prescribed quality indicators. Although this incentive design may encourage physicians to modify their behaviors and improve guideline adherence, the incentives are presently too few to sufficiently cover all activities in the P4P program.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the National Health Insurance Administration launched a pre-ESRD P4P program in 2006 and an early chronic kidney disease (CKD) P4P program in 2011 to deliver adequate care for patients with proteinuria or CKD. UPCR is a screening marker and is considered one of the inclusion indicators in these countrywide P4P programs for the patients with a risk of CKD progression 27 , 28 .…”
Section: Methodsmentioning
confidence: 99%